Sistem Informasi Manajemen Hubungan Pelanggan Berbasis Web Pada PT. Arya Media Tour & Travel - Ahmad Azizul Hakim; Singgi Pratama; Fransiska Prihatini S (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Tour & Travel is a company engaged in tourism services and services in and foreign services, booking airline tickets, hotel bookings, car rentals, and hajj / umroh services. This company has limited media promotional information, as a result, customers don't know the complete and correct information. In addition, this company can customize it, but not many customers know that. Customer complaints during the trip often do not go directly to the director, but customers always deliver it to tourguide. Development of applications to overcome these problems is to build a website-based customer relationship management information system with the method used is an iterative methodology consisting of the planning phase, problem analysis phase, design phase, implementation phase, and maintenance phase. This application uses the PHP programming language and uses the Notepad ++ program and MySQL as the database. With this application, it is expected to be able to assist in the delivery of information and help companies increase customer loyalty, attract new customers and retain existing customers in order to help each marketing process carried out by the company.